Analysis of the presence of women on the directors’ board and in senior management during the period 2015-2017 in companies listed on the Spanish Stock Exchange - Verona Martel, María Concepción (Universidad de Sonora, 2020)
The presence of women in the highest administrative and management bodies of companies has been found to be low in numerous studies carried out in different countries. In this work the situation in Spain is analyzed in the period from 2015 to 2017. The results show that the presence of women has increased on the board of directors and in the senior management of companies listed on the Spanish Stock Exchange, the increase being greater in the board of directors. However, there are still companies that do not have a female presence in either of these two bodies.